2017
DOI: 10.1371/journal.pmed.1002405
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis detection and the challenges of integrated care in rural China: A cross-sectional standardized patient study

Abstract: BackgroundDespite recent reductions in prevalence, China still faces a substantial tuberculosis (TB) burden, with future progress dependent on the ability of rural providers to appropriately detect and refer TB patients for further care. This study (a) provides a baseline assessment of the ability of rural providers to correctly manage presumptive TB cases; (b) measures the gap between provider knowledge and practice and; (c) evaluates how ongoing reforms of China’s health system—characterized by a movement to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 22 publications
3
124
0
1
Order By: Relevance
“…Studies have consistently shown large `know-do' gaps, or provider underperformance relative to their competence of appropriate care. 8,20,22,23 Although know-do gaps may be due to other factors such as lack of access to equipment or medication, prior studies consistently indicate that weak or misaligned incentives facing providers is a primary cause as significant gaps exist even in well-stocked settings. 24 China's difficulty in recruiting primary providers for rural areas may contribute to low provider performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have consistently shown large `know-do' gaps, or provider underperformance relative to their competence of appropriate care. 8,20,22,23 Although know-do gaps may be due to other factors such as lack of access to equipment or medication, prior studies consistently indicate that weak or misaligned incentives facing providers is a primary cause as significant gaps exist even in well-stocked settings. 24 China's difficulty in recruiting primary providers for rural areas may contribute to low provider performance.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] There is limited evidence, however, on the quality of primary care or its determinants in China's rural areas. While a few studies have examined care quality in certain regions of rural China, [8][9][10] no nationally representative studies have done so. To inform their efforts, policy-makers need a more comprehensive understanding of primary care quality and the barriers to its improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, referral links to the National Tuberculosis Programme are weak, with data from standardised patient studies in these three countries showing that only 28% to 45% of patients were correctly managed by primary care providers. 34,35,46 Simply put, the global capacity to diagnose, link to care, treat, and cure patients with tuberculosis is woefully inadequate for the massive burden of disease that exists. The public health implications, as well as the poor clinical and financial implications for patients, 41 are self-evident.…”
Section: Insufficient Investment and Political Willmentioning
confidence: 99%
“…Unfortunately, cascade of care analyses shows large gaps in the quality of care for both adults and children, and for both drug-susceptible and drug-resistant tuberculosis in many high-burden countries. [36][37][38]112,133 Standardised patient studies in India, Kenya, South Africa, and China [33][34][35]46 have shown that the quality of care for tuberculosis is poor. In a study in China, for example, health-care providers did not correctly manage patients presenting with archetypal symptoms or results suggesting active tuberculosis 59% of the time.…”
Section: Improving Quality Management To Ensure High-quality Service mentioning
confidence: 99%
“…They have shown that the quality of primary care in low-and-middle-income countries was poor. [11][12][13][14][15][16] Most cases were incorrectly diagnosed based on a very lenient definition, and simple medical conditions were improperly managed in the majority of cases. Antibiotics were usually inappropriately overprescribed, and it was less likely for primary care providers to refer patients to higher-level hospitals for specialist care when needed.…”
mentioning
confidence: 99%